2007
DOI: 10.1038/sj.jcbfm.9600311
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of Bone Marrow Stromal Cells Administered 1 Month after Stroke

Abstract: Bone marrow stromal cells (BMSCs) facilitate functional recovery in rats after stroke when administered acutely (1 day) or subacutely (7 days). In this study, we postponed the time of cell transplantation to 1 month after stroke. Female retired breeder rats were subjected to 2 h of middle cerebral artery occlusion (MCAo). Male BMSCs (3¾10 6 ) or phosphate-buffered saline were administered intravenously, and the animals were killed 3 months later. An additional population of nontreated rats was killed at 1 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
264
0
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(286 citation statements)
references
References 26 publications
8
264
0
12
Order By: Relevance
“…17,18 In addition, delayed treatment of stroke with MSCs at 7 days or at 1 month after stroke onset also increases brain plasticity and improves long-term functional outcome. 17,24,25 …”
Section: Msc Neurorestorative Therapymentioning
confidence: 99%
“…17,18 In addition, delayed treatment of stroke with MSCs at 7 days or at 1 month after stroke onset also increases brain plasticity and improves long-term functional outcome. 17,24,25 …”
Section: Msc Neurorestorative Therapymentioning
confidence: 99%
“…53 MSCs injected 1 month after stroke demonstrated positive effects in a chronic model with a reduction in scar thickness, increased proliferation of endogenous cells and oligodendrocyte precursor cells, and increased expression of the chemokine stromal cell-derived factor-1 (SCF1) along the ischemic boundary zone and its receptor on the MSCs. 54 Intracarotid transplantation in this model also markedly increased vessel sprouting, synaptophysin expression and the number of oligodendrocyte precursors in the corpus callosum, suggesting axon-myelin remodeling as a mechanism of action. 55 To examine these effects in long term, Chopp found that rats demonstrated significant improvement in neurological outcome at 4 months after transplantation, and showed increased growth-associated protein-43 (GAP43) expression (a marker of axonal growth cones) among reactive astrocytes in the scar boundary and subventricular zone.…”
Section: Nonhuman Mscsmentioning
confidence: 99%
“…Recombinant tissue plasminogen activator (rtPA), approved by the FDA in the treatment of ischemic stroke, is beneficial for the recovery of blood flow with no effect on the damaged neuronal tissue or vascular endothelium. Recent studies on stem cell therapy in animal models of stroke have revealed promising results (Bliss et al, 2007;Chen et al, 2001a, b;Shen et al, 2007b). Most of these studies used mesenchymal stem cells (MSCs) derived from bone marrow or umbilical cord blood.…”
Section: Introductionmentioning
confidence: 99%